Parkeringsnormen som ett styrmedel för en hållbar stad? - En fallstudie av parkeringsnormens inverkan på hållbarhet i Helsingborgs stad - Malmqvist,Frida (2017)
The problematic aspects of the car and car dependency in the cities form together one of the most central challenges when it comes to achieving sustainability in today’s society. This case study seeks to examine how regulations of minimum parking requirements affects the level of sustainability in the municipality of Helsingborg. The aim is to critically investigate the configuration of this planning document whose purpose is to enable parking in connection with new constructions. In addition to the parking requirements the municipalities usually, as in the case of Helsingborg, has a number of environmental related goals that needs to be fulfilled in order to achieve sustainability. It is therefore arguable that the municipal parking requirements are in conflict with the objectives of sustainability. The theoretical foundation of this thesis consists of David Harvey’s the right to the city and Bent Flyvbjerg’s theories concerning power relations in planning projects. The study also uses Torsten Hägerstrand’s time geography and path dependence-theory. Concerning empirical material the study uses documents regarding parking regulations and related political descisions together with interviews with planners and politicians. The results shows that the regulations of minimum parking requirements constitutes restrictions affecting the level of sustainability in Helsingborg in a number of ways.
Keywords: sustainability; Parking regulation; parking requirements; restriction; path dependence; Helsingborg